Neuromuscular fatigue induced by 90-minute soccer game - Robineau, J.; Jouaux, T.; Lacroix, M.; Babault, N. (The Journal of Strength and Conditioning Research, 2012)
This study aimed to quantify neuromuscular fatigue induced by a soccer game. Eight amateur soccer players (age 20.4 ± 1.3 years, mass 70.4 ± 6.9 kg, and height 174.9 ± 5.2 cm) reproduced a 90-minute soccer game modeling composed of two 45-minute periods separated by a 15-minute rest. Torque of quadriceps and hamstring muscle groups associated with electromyography, sprint speed, and vertical jump height was assessed before, at halftime, and immediately after the modeling. Most physical qualities decreased throughout the game with greater decays at match end than at halftime. Contrarily to quadriceps muscles, hamstring torque impairments were not accompanied by electromyographic activity reductions. Squat jump height was reduced at halftime and game end without any change for countermovement jumps. The sprint speed decrease was associated with stride frequency impairments without any change in amplitude and contact time. We concluded on torque production capacity and specific performance impairments during and after soccer games. Neuromuscular fatigue appeared primarily centrally mediated as attested by the reduced quadriceps muscle activity.